MEMBANGUN GENERASI MUDA MELEK KEUANGAN SYARIAH: IMPLEMENTASI PROGRAM SMART YOUTH, SMART FINANCE, DAN SMART FUTURE DI SMKN 1 BANTUL YOGYAKARTA - Novi Febriyanti; Anik; Ratih Purbowisanti; Ahmad Saifudin (DEVELOPMENT: Journal of Community Engagement, 2025)
This community engagement activity aims to strengthen Islamic financial literacy among students of the Accounting and Financial Institutions Department (AKL) at SMKN 1 Bantul through the program “Smart Youth, Smart Finance, Smart Future.” The program was implemented using a descriptive qualitative approach within a community service framework, employing interactive lectures, discussions, and reflective activities. Data were collected through observation, field notes, and documentation to capture participants’ responses and understanding. The results indicate that the program successfully enhanced students’ awareness of smart financial management based on Islamic principles, including distinguishing between needs and wants, avoiding consumptive behavior, and understanding the ethical and social dimensions of finance. Students also gained a broader perspective on financial planning and the importance of managing wealth responsibly and sustainably. Overall, this program demonstrates that Islamic financial literacy education delivered through participatory community engagement can effectively support the development of financially literate, ethical, and future-oriented youth.